Could FaRP-Like Peptides Participate in Regulation of Hyperosmotic Stress Responses in Plants? - Bouteau, François; Bassaglia, Yann; Monetti, Emanuela; Tran, Daniel; Navet, Sandra; Mancuso, Stefano; El-Maarouf-Bouteau, Hayat; Bonnaud-Ponticelli, Laure (Frontiers in Endocrinology, 2014)
The ability to respond to hyperosmotic stress is one of numerous conserved cellular processes that most of the organisms have to face during their life. In metazoans, some peptides belonging to the FMRFamide-like peptide (FLP) family were shown to participate to osmoregulation via regulation of ion channels; this is, a well-known response to hyperosmotic stress in plants. Thus, we explored whether FLPs exist and regulate osmotic stress in plants. First, we demonstrated the response of Arabidopsis thaliana cultured cells to a metazoan FLP (FLRF). We found that Arabidopis thaliana express genes that display typical FLP repeated sequences, which end in RF and are surrounded by K or R, which is typical of cleavage sites and suggests bioactivity; however, the terminal G, allowing an amidation process in metazoan, seems to be replaced by W. Using synthetic peptides, we showed that amidation appears unnecessary to bioactivity in A. thaliana, and we provide evidence that these putative FLPs could be involved in physiological processes related to hyperosmotic stress responses in plants, urging further studies on this topic.